Análise do discurso do trailer do filme We need to talk about Kevin, na perspectiva Foucaultiana - (:unkn) unknown (Universidade Federal do Pampa, 2014)
This present paper, appropriates of the discourse analysis on the Foucault's perspective, having as object of analysis the movie trailer of We need to talk about Kevin. According to Foucault, the discourse is shaped as a set of statements which takes basis in an same system of discursive formation; in that sense, it's important to reflect on the main concepts developed by the author, regarding the discourse, enunciation, discursive and non-discursive practices. At the end, shows that the enunciated is the main responsible for the signification of the discourse.
Keywords: Comunicação; Análise do discurso; Cinema; Foucault, Michel; Communication; CNPQ::CIENCIAS SOCIAIS APLICADAS